Adjunctive β2‐agonists reverse neuromuscular involvement in murine Pompe disease. Issue 1 (19th September 2012) - Li, Songtao; Sun, Baodong; Nilsson, Mats I.; Bird, Andrew; Tarnopolsky, Mark A.; Thurberg, Beth L.; Bali, Deeksha; Koeberl, Dwight D.
Abstract : Pompe disease has resisted enzyme replacement therapy with acid α‐glucosidase (GAA), which has been attributed to inefficient cation‐independent mannose‐6‐phosphate receptor (CI‐MPR) mediated uptake. We evaluated β2‐agonist drugs, which increased CI‐MPR expression in GAA knockout (KO) mice. Clenbuterol along with a low‐dose adeno‐associated virus vector increased Rotarod latency by 75% at 4 wk, in comparison with vector alone ( P <2×10 –5 ). Glycogen content was lower in skeletal muscles, including soleus ( P <0.01), extensor digitorum longus (EDL; P < 0.001), and tibialis anterior ( P <0.05) following combination therapy, in comparison with vector alone. Glycogen remained elevated in the muscles following clenbuterol alone, indicating an adjunctive effect with gene therapy. Elderly GAA‐KO mice treated with combination therapy demonstrated 2‐fold increased wirehang latency, in comparison with vector or clenbuterol alone ( P <0.001). The glycogen content of skeletal muscle decreased following combination therapy in elderly mice ( P <0.05). Finally, CI‐MPR‐KO/GAA‐KO mice did not respond to combination therapy, indicating that clenbuterol's effect depended on CI‐MPR expression. In summary, adjunctive β2‐agonist treatment increased CI‐MPR expression and enhanced efficacy from gene therapy in Pompe disease, which has implications for other lysosomal storage disorders that involve primarily the brain.—Li, S., Sun, B., Nilsson, M. I., Bird, A., Tarnopolsky, M. A., Thurberg, B. L., Bali, D., Koeberl, D. D. Adjunctive β2‐agonists reverse neuromuscular involvement in murine Pompe disease. FASEB J. 27, 34–44 (2013). www.fasebj.org